“O tempo é um búzio semente, plantado no peito do invisível. “Dança, tempo e ancestralidade entre criadores negres (2011 – 2021) - Mendes, Conceição de Maria Macau (2023)
The general objective of this research is to analyze the relationship between dance and ancestry in the formation and creation of black artists who work in cities in the northeast region, Elton Panamby and Inaê Moreira between 2011 and 2021. In addition to understanding the formative and creative paths of these artists, identifying how the element of sand present in their works relates to the notions of time and ancestry; and also problematizing the insertion of these artists into the so-called hegemonic circuit of contemporary arts, considering their entry strategies and the potential of the circulation of Afro-referenced narratives. The methodology applied here is crossed by black feminist influences, oral readings, autoethnographies and ancestry studies. It's worth noting that in no way is the intention here to standardize a territory, be it geographical, in this case the Northeast region; or sensitive and epistemic, when it comes to creation and afroreferences. It is not our interest to create formats, but rather to point out some practices that have shifted away from colonial aesthetic frameworks and regimes - recognized as classic languages.